Clinical Significance of Combined Anti-Cyclic Citrullinated Peptide Antibody and Rheumatoid Factor Assays in Rheumatoid Arthritis Diagnosis - Qingmei CAO,; Yanfeng WANG,; Yuanyuan JING, (Archives of Rheumatology, 2015)
Objectives: This study aims to investigate the value of combined anti-cyclic citrullinated peptide (CCP) antibody and rheumatoid factor (RF) assays in the clinical diagnosis of patients with rheumatoid arthritis (RA). Patients and methods: Results of both anti-CCP and RF detection in 70 RA patients (13 males, 57 females; mean age 49.2±12.1 years; range 35 to 61 years) and 112 non-RA patients (35 males, 77 females; mean age 42.5±7.1 years; range 35 to 49 years) were retrospectively and statistically analyzed. Results: In RA patients, positive rates of anti-CCP and RF were 70.0% and 77.1%, respectively. These rates were significantly higher than the rates in non-RA patients (2.7% and 4.5%, respectively; p<0.05). The sensitivity of combined anti-CCP and RF assays was 87.1% compared to the sensitivities of a single item assay of 70% and 77.1% for anti-CCP and RF, respectively. However, the combined assay had slightly lower specificity. With respect to the diagnostic index and rate of total consistency, the combined assay was superior to any single item assay. Conclusion: Combined anti-CCP and RF assays are more valuable in diagnosing RA than any single item assay.